(untitled) (Journal Of Educational and Psychological Researches, 2015)
This research aims to find out "the effectiveness of the self-questioning strategy in the achievement of students Phase III institutes of teacher preparation and decision-making in chemistry." The researcher follows approach quasi-experimental with a post-test, and the sample consisted of (27) from " Teachers Training Institute-AL-Byaa "in Directorate of Education Baghdad Karkh / 2 students divided into two unequal groups: experimental its number (14) students studied using reciprocal teaching strategy and control its number (13) students have studied in the usual way.The two groups were equivalent extraneous variables. The researcher was prepare achievement test consist of 40 items was the adoption of a measure of decision-making are from (20) paragraph and make for both validity and reliability and statistical analysis to items,The results of search was revealed Superiority of the experimental group that studied in accordance with the self-questioning strategy to a control group in the achievement and decision-making.